Against the Hounds of Hell : A Life of Howard Thurman - Eisenstadt, Peter R., 1954- (Book collections on Project MUSE., 2021)
"A biography of the American theologian and educator Howard Thurman. Thurman was a prominent African American civil rights leader who influenced many in his work for social justice, including Dr. Martin Luther King Jr"--